2021
DOI: 10.1029/2020jd033487
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian Perspective on Tropical Anvil Cloud Lifecycle in Present and Future Climate

Abstract: Tropical cloud radiative effects (CRE) are in deep convective regions determined by the relative proportions of thick, freshly detrained anvil clouds, and the thin anvils they evolve into. For thick anvil clouds, shortwave (SW) effects prevail over longwave (LW) effects, leading to a net climatic cooling effect. In contrast, LW effects prevail for thin anvil clouds with cloud optical depth (COD) smaller than 4, leading to a net warming effect (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 117 publications
5
8
0
Order By: Relevance
“…As previously shown (Cesana & Chepfer, 2012;Guzman et al, 2017;Stubenrauch et al, 2019), the model fails to reproduce the observed behavior of C THIN . Due to their different responses to SST variations, and to their different interactions with radiation and implications for weather and climate, our observations confirm that more attention should be paid to the evolution of the balance between opaque and thin high clouds with SST (Gasparini et al, 2019(Gasparini et al, , 2021Hartmann & Berry, 2017;Hartmann et al, 2001) on various time scales from instantaneous to diurnal, decadal and climate.…”
Section: Discussionsupporting
confidence: 63%
“…As previously shown (Cesana & Chepfer, 2012;Guzman et al, 2017;Stubenrauch et al, 2019), the model fails to reproduce the observed behavior of C THIN . Due to their different responses to SST variations, and to their different interactions with radiation and implications for weather and climate, our observations confirm that more attention should be paid to the evolution of the balance between opaque and thin high clouds with SST (Gasparini et al, 2019(Gasparini et al, , 2021Hartmann & Berry, 2017;Hartmann et al, 2001) on various time scales from instantaneous to diurnal, decadal and climate.…”
Section: Discussionsupporting
confidence: 63%
“…The number of RSP ice cloud observations within 500-m cloud top height bins over land and ocean surfaces is shown in Figure 2a. Similar to previous observations (Kubar et al, 2007; and model studies (Gasparini et al, 2021) of convective clouds, the number of observations peak at cloud top heights of around 12 km or 220 K, corresponding to the estimated level of neutral buoyancy (van . Compared to over land, relatively more cloud tops occur below the homogeneous freezing level over ocean, which is likely related to the weaker convection over ocean.…”
Section: Observational Resultssupporting
confidence: 84%
“…Most tropical radiative studies are confined to models. Looking at the CRE along Lagrangian trajectories in simulation, Gasparini et al (2021) found that large SW and LW values dominate close to convection as expected. The net CRE oscillates close to zero and is a function of the solar insolation.…”
Section: Introductionsupporting
confidence: 70%